Strategi Membangun Ekonomi Pesantren melalui Sentralisasi Kebutuhan Fashion Pada Industri Konveksi Pondok Pesantren Nurul Jadid - Ainol Yaqin; Lutfillah Lutfillah; Roisul Muhtadin (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2021)
The Nurul Jadid Islamic Boarding School has a large number of students and graduate, economic access to clothing (fashion) is widely used by external parties, even though the financial circulation is ini the same class as state educational institutions outside the Boarding School, on that basis, the head of the Boarding School, throung the business bureau, established a clothing industry factory for Nurul Jadid under name Germnet, the policy of the head of the pesantren requires the centralization of the one-stop clothing business to be hanlled by the Business bereau through the Garmen Nurul Jadid. This research is a qualitative research type of field research (field research), researchers lool foor a lot of data by by going directly to the research location to get primary information from the source, methods of analysis, this research has an important role for the economic progress of the Nurul Jadid Islamic Boarding Scholl. The formalations of this research include, Nurul Jadi made a profit of almos 1 billion so that she was the able to revive several pesantren sectors, developing pesantren human reseorces, the ability of students to reach the price of cloting, the life of intrepreneurial spirit from an early age and the economic development of the pesantren. This is only one economic sector, how about the economic sector for the needs of santri food, medical equipment, bathing, washing and others the Nurul Jadid Islamic Boarding School continues to make improvements.